Indicadores de sustentabilidade empresarial de boas práticas para micro e pequenas empresas: análise crítica e framework conceitual - Fonseca, Rita de Cassia (2020)
Environmental and social problems triggered by the decisions taken inside and outside the organizations and the scarcity of natural resources encouraged the use of practices to minimize the environmental impacts of business activities. Social problems, instigated by inequalities in living standards and widespread consumption in several countries, caused movements to emerge that highlight socioeconomic policies aligned with the search for proactive transformations. In this scenario of adversities, which aggravate environmental problems, new concepts arise with the society in the search for solutions and the creation of economic models aimed at future generations. However, there is still a lack of knowledge and commitment by micro and small companies to corporate sustainability that involves economic, social and environmental dimensions. From the perspective of the theory of sustainability, the analysis of the insertion of micro and small companies in routes for sustainability would allow a comparison with other types of companies, identifying the fragility of their actions in this field. This study aims, then, to critically analyze indicators of corporate sustainability, for the assessment of sustainable practices as a business strategy for micro and small companies, with a view to designing a conceptual framework of indicators that meet the reality of this segment. The research is of an applied and descriptive nature, starting from a bibliographic survey, using content analysis techniques with the support of the Nvivo 11 tool for analysis and exploration of the surveyed material; the treatment of the collected data is mixed, that is, both qualitative and quantitative, combining the potential of both. Based on the result of the analysis, using a Convergent Parallel Project, this work presents at the end a conceptual framework of sustainability indicators, with a critical analysis of them for micro and small companies. This framework brings, in principle, sustainability practices, which precede an organizational assessment using indicators.